Billionaire Island. Vol. 1 - Russell, Mark, 1971- (Ahoy Comics, 2020)
"Welcome to Billionaire Island, where anything goes...if you can afford it. But the island's ultra-rich inhabitants are about to learn that their ill-gotten gains come at a VERY high price."--Back cover of Volume 1.